Kawī Bhāī Wīra Siṅgha : Maṭaka hulāre, ika adhiaina - Bhāṭīā, Warindara Kaura (Paipasū Buka Ḍipū, 1979)
On the works of Bhai Bir Singh, 1872-1957, Panjabi litterateur, with reference to Maṭaka hulāre.